2019
DOI: 10.3390/cancers11081050
|View full text |Cite
|
Sign up to set email alerts
|

PD-L1 Blockade by Atezolizumab Downregulates Signaling Pathways Associated with Tumor Growth, Metastasis, and Hypoxia in Human Triple Negative Breast Cancer

Abstract: Triple negative breast cancer (TNBC) is the most aggressive type of breast cancer, which shows resistance to common breast cancer therapies, as it lacks the expression of the most common breast cancer targets. Therefore, TNBC treatment remains a challenge. Targeting programmed cell death-ligand 1 (PD-L1) by monoclonal antibodies (mAbs), for example, atezolizumab, has revolutionized the treatment for various cancer types. However, the therapeutic efficacy of targeting PD-L1 in TNBC is currently under investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 59 publications
(79 reference statements)
3
37
0
2
Order By: Relevance
“…While most pronounced effects were in fact seen in the combination therapy and thus interpretable as synergistic, the monotherapy itself modulated the tumor microenvironment. Anti-PD-L1 treatment induced genes relevant for autophagy and downregulated NF-κB-signaling, which is in line with data from a recent trial on triple negative breast cancer cells, treated with Atezolizumab [45]. Upon vaccination, matrix remodeling/metastasis-related genes and genes of the Wnt-and TGF-signaling were downregulated.…”
Section: Discussionsupporting
confidence: 86%
“…While most pronounced effects were in fact seen in the combination therapy and thus interpretable as synergistic, the monotherapy itself modulated the tumor microenvironment. Anti-PD-L1 treatment induced genes relevant for autophagy and downregulated NF-κB-signaling, which is in line with data from a recent trial on triple negative breast cancer cells, treated with Atezolizumab [45]. Upon vaccination, matrix remodeling/metastasis-related genes and genes of the Wnt-and TGF-signaling were downregulated.…”
Section: Discussionsupporting
confidence: 86%
“…Nevertheless, the role of PD-L2 in cancer progression is still unclear. On another note, phosphoinositide 3-kinase (PI3K) and mitogen-activated protein kinase (MAPK) are crucial oncogenic pathways that regulate PD-L1 expression [30]. Transcriptional PD-L1 is not only regulated by the PI3K pathway [31], but also regulated by signal transducer and activator of transcription 3 (STAT3) [32], nuclear factor kappa B (NF-κB) [33], and B-cell CLL/lymphoma 3 (Bcl3) proto-oncogene [34].…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that BKM120 upregulated the mRNA expressions of proapoptotic genes and diminished the transcription of antiapoptotic target genes of NF-κB ( Figure 5A). Based on our findings and with reference to the considerable studies pointing to the tight crosstalk between NF-κB and the PI3K pathway [24], we examined the effect of NF-κB suppression on the anticancer impact of the inhibitor. Our results showed that the suppression of NF-κB using a well-known proteasome inhibitor, bortezomib, amplified the repressive effect of the PI3K inhibition on KG-1 cell survival ( Figure 5B).…”
Section: Alteration Of Apoptosis-related Genes Upon Treatment Of Kg-1mentioning
confidence: 99%